Absent Schlemm's Canal With Reduction in Intraocular Pressure Through Uveoscleral Pathway Observed After Conditional Deletion of AP-2β in the Mouse - Dham, Japnit (My University, 2022)
A unique mouse model recently developed in our laboratory (AP-2β TMR-KO) achieves a conditional deletion of transcription factor AP-2β from the developing periocular mesenchyme and its derivatives using MgpCre/loxP technology. These mutants fail to develop SC and exhibit increased IOP, which temporarily reduces with latanaprost treatment. Here we have shown changes in protein and gene expression of various SC markers. Specifically, Prox1 expression was detected in the wildtype at P4, P10, and P14, but was absent in the AP-2β TMR-KO mice at those stages. Klf4 expression was not present in either wildtype or mutant at P4 but was detected at P10 and P14 in the wildtype only. Additionally, decreased gene expression was observed of Prox1, Klf4, and Tie2 in the SC region at P4 and P10, and of Angpt1 in the trabecular meshwork region, in mutant eyes. Furthermore, dextran tracer studies were performed to assess aqueous outflow in wildtype and AP-2β TMR-KO mice; dextran was detected in regions of both outflow pathways in the wildtype but was clustered in the anterior chamber in the mutant, with the corrected total fluorescence significantly higher in the anterior chamber and significantly lower in regions of outflow for the mutant relative to wildtype. Upon latanaprost treatment, dextran was similarly present in the wildtype, but detected further along the uveoscleral pathway in the mutant with time. The data generated in this project provides more insight into the role of AP-2β in the development and function of the aqueous humor outflow pathways. This information will be critical to elucidating the genetic cascade through which AP-2β regulates anterior segment development. Additionally, this project points to the potential of the AP-2β TMR-KO mice as a model for glaucoma.